Acute papillary stone impaction: An ideal indication for upfront needle knife papillotomy (“needle knife excision”) - Vincent Zimmer (Clinical Case Reports, 2021)
Abstract Needle knife papillotomy (NKP) is still considered a rescue technique after conventional access failure due to traditional high complication rates, albeit data are maturing for early use of NKP in standard endoscopic retrograde cholangiopancreatography indications. By contrast, in certain settings NKP should be prioritized to a first‐class indication, such as in choledochocele management and/or, more often encountered in clinical practice, true papillary stone impaction with or without gallstone pancreatitis. The latter results in prompt stone release; thus, the procedure might become alternatively designated as “needle knife excision.”